The influence of violence and sexism on Mexican women who have experienced intimate partner violence - Rodríguez Muñoz, Carolina; Reyes-Sosa, Hiram (Pensando Psicología, 2025)
Intimate partner violence has negative short- and long-term effects on the community, primarily on women. Therefore, it is necessary to conduct studies that analyze why a woman decides to seek help in order to break the cycle of violence. This study aims to explain the effect of the prevalence and severity of different types of violence, levels of sexism, and domestic violence experienced during childhood on the formal and informal help-seeking patterns of Mexican women who requested support from a social organization. A non-probability sample of 70 women with a mean age of 35 years (SD = 9.90) participated in this research. The results showed the importance of minor and severe injuries in the decision to seek formal services. In turn, levels of sexism and violence experienced or observed within the family do not impact any type of help (formal or informal). This study demonstrates the importance of analyzing this type of population to better understand the phenomenon of intimate partner violence and how help-seeking functions differently.
Keywords: intimate partner violence; help-seeking behaviors; domestic violence; sexism